Characterization of a Urochloa humidicola methanol extract as a phytogenic additive for ruminants (Bioscience Journal, 2017)
This survey aimed to characterize a Urochloa humidicola methanol extract regarding the presence of secondary metabolites classes and to determine its bromatological composition. U. humidicola samples were dried under shade, milled on a 2-mm sieve by a Willey mill. The solution obtained was filtered using filter paper and concentrated in a rotary evaporator under reduced pressure; the concentrated residue was then placed in an open vessel to complete solvent removal using continuous air flow dryers. Phytochemical prospection tests and bromatological composition analyses were performed on the dry methanol extract, and the results were compared to in natura U. humidicola. The methanol extract had 10.2% CP and 35% EE and in natura U. humidicola had 5.17% CP and 1.57% EE, with a difference (P < 0.05) of 5% by Fisher's test. In natura U. humidicola had 75.59% NDF, 40.77% ADF, 38.82% HEM, 29.93% CEL, and 7.19% LIG. Methanol extraction by cold maceration reduced the LIG (0.17%) and CEL (0.21%) contents as only soluble constituents were extracted. A phytochemical assay was positive for the presence of saponins, tannins, alkaloids, non-protein amino acids, carbohydrates, cardiac glycosides, steroids, tripernoids, catechins, and saccharides and was negative for the presence of flavonoids and purines. The U. humidicola methanol extract possesses traits that allow its use as a phytogenic and natural additive.